2016
DOI: 10.1007/5584_2016_42
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Next-Generation Sequencing Metagenomic Analysis for Detection of RNA and DNA Viruses in Cerebrospinal Fluid: The Confounding Effect of Background Contamination

Abstract: Next-generation sequencing (NGS) followed by metagenomic enables the detection and identification of known as well as novel pathogens. It could be potentially useful in the diagnosis of encephalitis, caused by a variety of microorganisms. The aim of the present study was to evaluate the sensitivity of isothermal RNA amplification (Ribo-SPIA) followed by NGS metagenomic analysis in the detection of human immunodeficiency virus (HIV) and herpes simplex virus (HSV) in cerebrospinal fluid (CSF). Moreover, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…This discrepancy could be due to the fact that metagenomic workflows are less sensitive than specific real time RT-PCR/PCR assays and thus may fail in analysis of low viral-copy CSF samples [ 52 ]. Using serial dilutions of HIV and HSV positive sera in negative CSF, we have previously found that the limit of detection was 10 2 and 10 3 copies per reaction, respectively, while in the current study viral load in metagenomics-negative real-time PCR-positive samples ranged from 550 to 1650 copies/ml [ 53 ].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This discrepancy could be due to the fact that metagenomic workflows are less sensitive than specific real time RT-PCR/PCR assays and thus may fail in analysis of low viral-copy CSF samples [ 52 ]. Using serial dilutions of HIV and HSV positive sera in negative CSF, we have previously found that the limit of detection was 10 2 and 10 3 copies per reaction, respectively, while in the current study viral load in metagenomics-negative real-time PCR-positive samples ranged from 550 to 1650 copies/ml [ 53 ].…”
Section: Discussionmentioning
confidence: 62%
“…These mostly represented phage species and artifact sequences, which are particularly common for samples with a low DNA and RNA loads [ 54 , 55 ]. Moreover, the reagents themselves could be the source of contaminating foreign sequences and may affect the interpretation of metagenomic results [ 53 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of sequences (usually > 99%) come from human hosts, consequently limiting the overall analytical sensitivity of pathogen detection methods [33] . Another potential challenge is that testing samples, reagents, or contaminating microorganisms in the laboratory environment can affect the accuracy of results [34,35] . In addition, while metagenes can be used to detect pathogenic bacteria, they cannot be used for drug sensitivity tests at the same time, which remains a persistent issue.…”
Section: Resultsmentioning
confidence: 99%
“…One major downside to shotgun metagenomics is the interference with human DNA and environmental contaminants [89][90][91][92]. Specimen pre-processing can increase pathogen-to-human DNA ratio, allowing for increased pathogen detection sensitivity and reduced human sequences [93].…”
Section: Sequencingmentioning
confidence: 99%